The Retention of Adult Sport Participants: The Challenge of Player Ratings - Edward Horne; Matthew Brown (Journal of Applied Sports Management, 2019)
The current study investigates the retention of competitive tennis players in the United States Tennis Association’s (USTA’s) adult league system to answer the following questions: What factors do participants identify as impactful to their participation in adult league tennis? How do participants believe these factors impact their retention? Results suggest participants believe the current system fails to incentivize development as competitors fail to transition successfully to a higher rating and struggle socializing into a new team. Competitors therefore seek to cheat the system. The current study illustrates the importance for league policymakers to consider unintended consequences and provides recommendations. Subscribe to JASM
Keywords: Adult sport; participation; retention; sport development; tennis